Using MDA for Building Wireless Sensor Network Applications - Rodrigues, Taniro C.; Dantas, Priscilla V.; Delicato, Flavia C.; Pires, Paulo F. P.; Miceli, Claudio; Pirmez, Luci (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2010: Anais do IV Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2010)
We propose a MDA approach to develop WSN applications, which allows domain experts to contribute in the development of applications without needing knowledge on WSN platforms and allows network experts to program nodes to met application requirements without specific knowledge on the domain. Our approach also promotes reuse, allowing an application model to be reused across different sensor platforms and a platform model to be reused for different applications.